calcular a distância do ponto B(-1,-3) até o ponto C(2,6)
Soluções para a tarefa
Respondido por
0
Resposta:dB,C=10u.c.
Explicação passo a passo:
dB,C=![\sqrt{(xC-xB)^{2}+(yC-yB)^{2} } \sqrt{(xC-xB)^{2}+(yC-yB)^{2} }](https://tex.z-dn.net/?f=%5Csqrt%7B%28xC-xB%29%5E%7B2%7D%2B%28yC-yB%29%5E%7B2%7D++%7D)
dB,C=
dB,C=
dB,C=
dB,C=10u.c.
Respondido por
0
Resposta:
dB,C=10u.c.
Explicação passo a passo:
dB,C=\sqrt{(xC-xB)^{2}+(yC-yB)^{2} }
(xC−xB)
2
+(yC−yB)
2
dB,C=\sqrt{(2-(-1))^{2} +(6-(-3))^{2} }
(2−(−1))
2
+(6−(−3))
2
dB,C=\sqrt{(9)+(81)}
(9)+(81)
dB,C=\sqrt{100}
100
dB,C=10u.c.
Perguntas interessantes
ENEM,
6 meses atrás
Biologia,
6 meses atrás
Psicologia,
6 meses atrás
Matemática,
7 meses atrás
Administração,
7 meses atrás
Filosofia,
1 ano atrás